Studies of colletotrichum species causing cowpea anthracnose in Nigeria reveal two first-time reports globally - Dada, A. O.; Dania, V. O.; Oyatomi, O.; Abberton, M.; Ortega-Beltran, A (2024)
Cowpea (Vigna unguiculata (L.) Walp.) is an important multipurpose crop in various countries in sub-Saharan Africa. However, cowpea production is affected by cowpea anthracnose disease (CAD). In Nigeria, Colletotrichum lindemuthianum and C. destructivum have been described as causal agents of CAD based on morphological features. Such characterization is unreliable because many similarities among and within Colletotrichum spp. exist. In the current study, Colletotrichum spp. were isolated from leaves showing CAD symptoms collected in farmers’ fields across four states in Nigeria. Isolates were characterized using morphological keys, severity scores in detached leaf assays, and sequencing of the ITS, ACT, GADPH, TUB, ApMat, and CAL genes. Two species, C. chrysophilum and C. siamense, were identified after comparing multigene sequences. Morphological characteristics and disease symptoms were very similar for both species. However, severity scores varied among and within species. Both C. chrysophilum and C. siamense are reported for the first time as causal agents of CAD across the globe. The accurate diagnosis of organisms causing CAD in the studied region will allow developing effective management strategies.